2008
DOI: 10.1371/journal.pone.0003319
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Natalizumab Treatment on Foxp3+ T Regulatory Cells

Abstract: BackgroundNatalizumab, a monoclonal humanized antibody targeting the alpha-4 chain of very late activation antigen 4 (VLA-4) exerts impressive therapeutic effects in patients with relapsing-remitting multiple sclerosis. Our objective was to study impacts of Natalizumab therapy on Foxp3+ T regulatory cells (Tregs) in multiple sclerosis (MS) patients.MethodologyA combined approach of in vitro and ex vivo experiments using T cells isolated from the peripheral blood of healthy donors and Natalizumab treated MS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 39 publications
7
45
2
2
Order By: Relevance
“…In addition, Tregs may be ‘recruited’ to migrate into the CNS at times of inflammation and may modulate the function of effector cells in the CNS, which suggests a role in the immune surveillance in the CNS [20]. Our finding is somewhat different from the one of Stenner et al [27] who did not find an impact of natalizumab on Treg frequency. One explanation may be that the definition of Tregs may be different – Stenner et al measured CD25 high -expressing Tregs.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In addition, Tregs may be ‘recruited’ to migrate into the CNS at times of inflammation and may modulate the function of effector cells in the CNS, which suggests a role in the immune surveillance in the CNS [20]. Our finding is somewhat different from the one of Stenner et al [27] who did not find an impact of natalizumab on Treg frequency. One explanation may be that the definition of Tregs may be different – Stenner et al measured CD25 high -expressing Tregs.…”
Section: Discussioncontrasting
confidence: 79%
“…One explanation may be that the definition of Tregs may be different – Stenner et al measured CD25 high -expressing Tregs. This study, however, reported on the effect of a single infusion on Tregs [27]. It is noteworthy that 5 of 15 patients had a decrease in CD4+CD25+FoxP3+ Treg frequency in this study.…”
Section: Discussionmentioning
confidence: 70%
“…ϩ frequency or suppressive activity either in vitro or in vivo (79). Moreover, there was no preferential blockade or permissiveness for the transmigration of Tregs into tissues compared with conventional T cells.…”
Section: Foxp3mentioning
confidence: 93%
“…Natalizumab is an ␣4 (VLA4) integrin antagonist that selectively blocks trafficking of leukocytes to inflamed tissues and that may also play a role in co-stimulatory signals for T cells (79). Major concerns were raised about this molecule in 2005 after cases of PML were reported (80 -82).…”
Section: Natalizumab (Tysabri)mentioning
confidence: 99%
“…23f). TREG have previously been shown to express relatively low levels of VLA-4 (Stenner et al 2008), a finding supporting the observation in our study. We also observed a significant decrease in terminally differentiated, senescent CD8 + CD28 -CD57 + cells after treatment (Fig.…”
Section: Natalizumab Effects On Lymphocyte Subpopulations (Paper Iii)supporting
confidence: 93%